A novel architecture of dandelion-like Mo2C/TiO2 heterojunction photocatalysts towards high-performance photocatalytic hydrogen production from water splitting. Issue 21 (17th May 2017) - Yue, Xinzheng; Yi, Shasha; Wang, Runwei; Zhang, Zongtao; Qiu, Shilun
Abstract : The well-designed Mo2 C/TiO2 hierarchical configuration exhibits extremely high photocatalytic H2 production activity from water splitting. Abstract : In the development of photocatalytic hydrogen (H2 ) production, designing and optimizing photocatalyst nanostructures with efficient charge transfer and separation for catalytically active sites are still a great challenge. Herein, a well-controlled synthetic strategy is developed to prepare an Mo2 C/TiO2 hetero-nanostructure, in which the TiO2 3D hierarchical configuration is loaded with highly dispersed Mo2 C nanoparticles. This heterostructure achieves the excellent photocatalytic activity of 39.4 mmol h −1 g −1 with its rate ∼25 times higher than that of pristine TiO2 . Also, our photocatalysts process excellent long-term durability (>20 h). The impressive photocatalytic H2 activity of Mo2 C/TiO2 indicates favourable charge carrier dynamics, as determined by the results of photoluminescence (PL), time-resolved photoluminescence (TRPL), surface photovoltage (SPV), and open circuit potential (OCP) decay curves. Moreover, this study provides a guide for researchers to design new functional materials with excellent hydrogen production activity.